Evaluación de edificaciones in situ según las normas NEC después de un evento sísmico. - Mora Valverde, Freddi Marcelo (2017)
In the present work, an applied model for the evaluation of in situ constructions according to the Ecuadorian norm of the construction NEC - 2015 after a seismic event, based on the use of conceptual elements, documentaries, observations and investigations with the Which is an instrument that allows an efficient and orderly evaluation process to be carried out with the objective of identifying safe buildings that can continue to function for people who are victims of seismic events. The result of this research we will use the FEMA-154 method to make the rapid visual evaluation of seismic vulnerability for buildings after an earthquake and in case it exceeds the vulnerability indexes a detailed evaluation of the building will be made, which can be done Lasting hours, days or weeks.